Dietary Supplement for Core Symptoms of Autism Spectrum Disorder: Where Are We Now and Where Should We Go? - Li, Yong-Jiang; Ou, Jian-Jun; Li, Ya-Min; Xiang, Da-Xiong (Frontiers in Psychiatry, 2017)
Autism spectrum disorders (ASDs) are a class of severe and chronic conditions and core symptoms are deficits in social interaction, language communication impairments, and repetitive/stereotyped behavior. Given the limitations of available treatments and substantially increased prevalence of the disease, additional interventions are needed. Since the use of dietary supplements for ASD is of high prevalence, up-to-date information about those supplements are required for both parents and clinicians. Relevant articles were identified through a systematic search of PubMed, EMBASE, Cochrane library, and PsychINFO databases (through May 2017). Current best evidences of 22 randomized controlled trials on 8 different dietary supplements for core symptoms of ASD were reviewed. For each supplement, this report focuses on the definition and potential therapeutic mechanisms, the latest advances, and discussion of study limitations and future directions. Most studies were small and short term, and there is little evidence to support effectiveness of dietary supplements for children with ASD.